Rational emotive behavior therapy in sport and exercise - Turner, Martin; Bennett, Dick (Routledge psychology of sport, exercise and physical activity, 2018)
Rational Emotive Behaviour Therapy (REBT) is one of the most widely used counselling approaches in the world and is one of the original forms of Cognitive Behavior Therapy (CBT). It brings together leading international experts and practitioners to reflect on the use of REBT in sport and exercise, and examine the techniques used. Each chapter contains a case study, contextualising theory into practice, giving a rare and detailed insight into the use of REBT across a diverse range of issues.